The application of reality therapy and behavioral counseling in the guidance program of Divine Word College of Bangued-college department - Buenafe, Imelda Carmen A. (Animo Repository, 1976)
The primary purpose of this study it to pave the way for the establishment of a guidance program in the college department of Divine Word College of Bangued and an in-service training for teachers with emphasis on reality therapy and behavioral counseling for effective classroom management. Based on the writers limited knowledge and impressions of the needs of the college department and as revealed by the Minnesota Counseling Inventory and the Inventory on Teacher and Student Awareness on Guidance, the program was developed. General and specific objectives were set up to provide direction for the study. The main topics of the in-service program include : 1) general concepts, principle and practices of guidance, 2) guidance program and its services, 3) Reality Therapy and Behavioral Counseling.